Pemanfaatan Belimbing Wuluh (Averrhoa Bilimbi L) dan Minyak Zaitun untuk Masker Perawatan Kulit Wajah - Rahmasari, Ella Novia; Puspitorini, Arita (Journal of Beauty and Cosmetology (JBC), 2020)
Skin is the outermost layer covering the body. Skin needs the care to keep it clean and healthy. Skincare can be done in various ways, including using natural masks. Natural masks are masks made from natural ingredients and processed by yourself. One of the facial treatments using natural face masks is to use wealth starfruit and olive oil. So far, wuluh starfruit is known as an ingredient for cooking. But it turns out that wuluh starfruit contains compounds that are good for facial skincare, such as flavonoids, tannins, saponins, triterpenoids, glucose, peroxides, and formic acid which are useful for reducing acne. In addition, wuluh starfruit also contains high calcium, protein, iron, and phosphorus as well as vitamins A, B1 and C. Then olive oil in addition to cooking, is also very useful for facial skincare because of its high content of antioxidants and vitamin E. This study aims to measure the use of a mask of wuluh starfruit and olive oil. The method used in this research is the literature review method by collecting data using the technique of searching for topics among several kinds of literature and taking them. The results of this study were to utilize a mask of wuluh starfruit and olive oil.Keywords: facial mask, wuluh starfruit, and olive oil.